Estimating the efficiency of primary health care services and its determinants: evidence from provincial panel data in China - Zhao, Zhe; Dong, Silai; Wang, Jiahe; Jiang, Qingzhi (Frontiers in Public Health, 2023)
Background The efficiency of primary health care services is drawing increased attention worldwide, especially in developing countries. Health care reform in China has moved into the ‘deep water zone’ phase and is facing the dilemma of inefficiency in primary health care services, which is a critical challenge for universal health coverage. Methods In this study, we estimate the efficiency of primary health care services in China and its determinants. A combination of a super-SBM (Slack-Based Measure) model, a Malmquist productivity index model and a Tobit model is used to study provincial panel data, and the results demonstrate the inefficiency of primary health care services in China and the variations in efficiency values between regions. Results Over time, the productivity of primary health care services shows a decreasing trend, mainly due to slowing technology change. Financial support is needed to improve the efficiency of primary health care services, but it is worth noting that existing social health insurance coverage decreases efficiency, while economic development, urbanization and education also have a significant impact. Conclusion The findings suggest that increasing financial support should remain a priority in developing countries but that reasonable reimbursement design, appropriate payment methods and comprehensive supporting social health insurance policies are key to the next step of reform.